Are women better leaders?: the perspectives of employees - Nur Saleeza, Binti Mohamad Saleh (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study aimed to explore the perception of employees towards women leadership in an organisation. This study was done in two departments in University Malaysia Sarawak (UNIMAS) which are human resources and bursary department. The objectives of this study is to explore the acceptance of employees' on having a female leader. Other than that, this study also aimed to identify employees' perception towards the advantages that they gain from having a female leader and to analyse their perception towards the effect of female leadership style towards theirs and organisation performances. This study managed to get seven informants through purposive and snow ball sampling. Research instrument used in this study is semi-structured interview questions. Findings within this research have been supported by previous past research that related to this topic. Based on the data collected and the research findings, several recommendations have been proposed to the organisation, women leaders and future researchers. Organisation should take the perception of employees towards women leadership a serious matter so that the organisation can be run smoothly. The women leaders should consider the comments from employees so that they can improve their leadership style. For future researchers, they should conduct this kind on research by using mix method so that it could enhance the quality of findings.